Sirtuin 5 depletion impairs mitochondrial function in human proximal tubular epithelial cells - Haschler, Timo N. (Sci Rep, 2021)
Ischemia is a major cause of kidney damage. Proximal tubular epithelial cells (PTECs) are highly susceptible to ischemic insults that frequently cause acute kidney injury (AKI), a potentially life-threatening condition with high mortality. Accumulating evidence has identified altered mitochondrial function as a central pathologic feature of AKI. The mitochondrial NAD(+)-dependent enzyme sirtuin 5 (SIRT5) is a key regulator of mitochondrial form and function, but its role in ischemic renal injury (IRI) is unknown. SIRT5 expression was increased in murine PTECs after IRI in vivo and in human PTECs (hPTECs) exposed to an oxygen/nutrient deprivation (OND) model of IRI in vitro. SIRT5-depletion impaired ATP production, reduced mitochondrial membrane potential, and provoked mitochondrial fragmentation in hPTECs. Moreover, SIRT5 RNAi exacerbated OND-induced mitochondrial bioenergetic dysfunction and swelling, and increased degradation by mitophagy. These findings suggest SIRT5 is required for normal mitochondrial function in hPTECs and indicate a potentially important role for the enzyme in the regulation of mitochondrial biology in ischemia.